Unsuccessful Intubation and Stabilization by Laryngeal Mask Airway in the Delivery Room: A Case of Tracheal Atresia - Mark Cody Smith; Autumn Kiefer; C. Eric Bailey (Case Reports in Pediatrics)
A term male newborn infant was apneic at birth, and endotracheal intubation was unsuccessful. He was stabilized for transport with a laryngeal mask airway. Laryngoscopy revealed tracheal atresia with intrathoracic distal tracheoesophageal fistula. A laryngeal mask airway may provide ventilation in tracheal atresia patients with a fistula.